Burning Man art, politics and economics in a matrix of contemporary corporate and cybernetic relations: Burning Man: art, politics and economics in a matrix of contemporary corporate and cybernetic relations (Simbiótica. Revista Eletrônica, 2023)
This article discusses the Burning Man festival, founded in 1986 and held annually in the Black Rock desert (USA), as an open-air social and technological laboratory, from which ideological and technical guidelines of the contemporary corporate and cybernetic world are derived. It begins with a detailed description of the festival's historical genesis and its guiding principles to understand the incorporation of Burning Man by Silicon Valley managers, with emphasis on the influence that the festival have on Google and its particular forms of work organization and cybernetic technology. From this specific relationship, we reach an understanding of Burning Man as a large-scale “cultural infrastructure”, correlated with the contemporary injunctions that invade the world of labor and networks.